Science and omniscience in nineteenth-century literature - Taylor, Jonathan (Sussex Academic Press, 2007)
On history, chaos, and Carlyle – On cosmology, heresy, Abbott, and Poe – On microcosms, macrocosms, and the music of the spheres – Afterword : a note on omniscient narrators
9781845191252
Keywords: Laplace; Pierre Simon; Carlyle; Thomas; Abbott; Edwin Abbott; Poe; Edgar Allan; Dickens; Charles; Laplace; Pierre Simon 1749-1827; Carlyle; Thomas 1795-1881; Abbott; Edwin Abbott 1838-1926; Poe; Edgar Allan 1809-1849; Dickens; Charles 1812-1870; Essai philosophique sur les probabilités; Old curiosity shop; English literature; Literature and science; Omniscience (Theory of knowledge) in literature; Determinism (Philosophy); Music and science